ModVizPop: A shiny interface for empowering teams to perform interactive pharmacokinetic/pharmacodynamic simulations. (21st August 2021) - Vaddady, Pavan; Kandala, Bhargava
Abstract: ModVizPop is an interactive and dynamic visualization tool developed for simulating differential equation–based population pharmacokinetic (PK) and pharmacodynamic (PD) models with variability. It has a built‐in PK/PD ordinary differential equations library of models to choose from alongside the ability to plug in a user‐defined model from a local or project directory. The user interface consists of several key inputs for performing the simulations as well as options to visualize the plots, perform simple noncompartmental analysis, and review inputs and model code. It also provides the ability to download the underlying model, plots, simulated data, or a comprehensive report consisting of all the key inputs and outputs of the simulations. The interface includes advanced features where users can overlay external data on a simulation, set a certain simulation scenario as a reference, or carry out sensitivity analysis–based simulations. This easy‐to‐use interface can serve as a valuable tool to project teams to evaluate potential scenarios facilitating collaborative decision making in the drug discovery and development paradigm.